Treatment-Seeking Behaviour of the Homeless in Madiun City, East Java, Indonesia - Ratnawati, Riska; Kurniasih, Erwin (Universitas Muhammadiyah Surakarta, 2020)
Background: The health services can be utilized for all the people who need them. But for certain community like homeless can’t get a good health services because they don’t have to access them. The problems for homeless are knowledge, attitudes, affordability of health services, peer group support, health personnel support, and income. The objective of research is to know the factors affected health seeking behaviour of homeless in Madiun City.Method: The method used was analytic survey with a cross-sectional study design. The sample was the homeless in Madiun City totalling53 respondents, both male and female with accidental sampling. The data were collected by using questionnaire and analysed by using bivariate analysis with Chi-Square statistical test (X2).Results: The results showed that variables which affected the homeless’ health seeking behaviour were knowledge, (ρ-value = 0.001 < α = 0.05), attitude (ρ-value = 0.000 < α = 0.05), and health service affordability (ρ-value = 0,000 < α = 0.05). Meanwhile, the variables which did not affect the homeless’ health seeking behaviour was the provision of health service (ρ-value = 0.561 > α = 0.05). It conclude that knowledge, attitudes, affordability of health services, peer group support, health personnel support, and income were proved to be factors that increased the search for assistance to the homeless people in Madiun City.